A visual programming framework for distributed Internet of Things centric complex event processing. (March 2019) - Gökalp, Mert Onuralp; Koçyiğit, Altan; Eren, P. Erhan
Abstract: Complex Event Processing (CEP) is a promising approach for real-time processing of big-data streams originating from Internet of Things (IoT) devices. Even though scalability and flexibility are key issues for IoT applications, current studies are mostly based on centralized solutions and restrictive query languages. Moreover, development, deployment and operation of big-data applications require significant amount of technical expertise. Hence, a framework that provides a higher abstraction level programming model and a streamlined execution environment is essential to facilitate widespread user adoption. In this paper, we propose a data-flow based visual programming model that enables development of big-data applications in IoT domain even by users who have limited or no experience in big-data technologies. A scalable CEP engine is also devised to execute the applications developed using this language. A prototype is implemented by using the state-of-the-art big-data and real-time stream processing technologies to evaluate the applicability and usability of the framework.